Digital Processes for the Redevelopment of Social Housing in Plattenbau - Marina Block; Massimo Perriccioli; Monica Rossi-Schwarzenbeck (Agathón)
As part of a framework agreement between the DiARC of the ‘Federico II’ University of Naples and the Fakultät Bauwesen of the HTWK Leipzig, which led to a collaboration with the LWB – the public housing manager of the city of Leipzig which for years has implemented a policy of redevelopment and management of the Plattenbauten housing heritage carried out after the war – an experimental research is underway for developing process innovations related to documentation, redevelopment and management of social housing. The goal is to propose, through digital and computational technologies, smart design solutions that make this heritage responsive to increasingly changing and indeterminate contexts and encourage new interactions between stakeholders involved in the different stages of the process.